TCP transcription factors in action: shaping floral traits and inflorescence architectures - Xuan Hu; Yuyang Wang; Yafei Zhao (Ornamental Plant Research)
TCP transcription factors are plant-specific regulatory proteins known to play major roles in controlling floral traits and inflorescence architecture. This review highlights the recent advancements in understanding the multifaceted roles of TCP genes in floral symmetry establishment, pseudanthia development, and regulation of floral pigmentation. The review examines the interplay between the TCP proteins and other gene families, such as MADS-box and MYB transcription factors, to shape floral morphology. Specifically, we explore how TCP transcription factors influence downstream genes associated with pigment biosynthesis and affect floral orientation. The current understanding of TCP genes serves as a basis for designing molecular breeding strategies to create desired floral features that enhance both fitness and aesthetic value.